2001
DOI: 10.1007/s00441-001-0475-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal treatment with somatotropin during early gestation affects basic events of myogenesis in pigs

Abstract: The effects of maternal treatment with somatotropin during early gestation on fetal muscle development were determined. Crossbred gilts received daily injections of either 3 ml of a placebo ( n=31) or of 6 mg porcine somatotropin ( n=31) from day (d) 10 to 27 of gestation and samples were collected from d 28 embryos, d 37 and 62 fetuses, and from neonates. Administration of somatotropin increased the total number of fibres (primary and secondary fibres) in neonatal semitendinosus muscle of middle- and low-weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
(49 reference statements)
2
20
0
Order By: Relevance
“…Indeed, daily injections of growth hormone (GH) in the sow during early pregnancy has been shown to enhance foetal fibre number (Rehfeldt et al, 2001), an effect likely to be mediated by IGF-1. IGF-1 and -2 stimulate both muscle cell proliferation and differentiation through the interaction with the type 1 IGF receptor (IGF1R), insulin receptor exon 11-(IR-A) and insulin receptor exon11 þ (IR-B), all of which are transmembrane tyrosine kinase receptors (Denley et al, 2005).…”
Section: Fibre Number: Mediators Of Muscle Hyperplasiamentioning
confidence: 99%
“…Indeed, daily injections of growth hormone (GH) in the sow during early pregnancy has been shown to enhance foetal fibre number (Rehfeldt et al, 2001), an effect likely to be mediated by IGF-1. IGF-1 and -2 stimulate both muscle cell proliferation and differentiation through the interaction with the type 1 IGF receptor (IGF1R), insulin receptor exon 11-(IR-A) and insulin receptor exon11 þ (IR-B), all of which are transmembrane tyrosine kinase receptors (Denley et al, 2005).…”
Section: Fibre Number: Mediators Of Muscle Hyperplasiamentioning
confidence: 99%
“…The range of biological effects of PST is extraordinary and has been discussed previously (Rehfeldt et al, 2001). Early studies by Lary established that PST worked in pigs (Harrelll et al, 1996;Etherton, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…The greater IGF-I concentrations in GM than in LW gilts was not reported in boars (Louveau et al 1991) or late-pregnant gilts (Farmer et al 2000), but was recently observed in gilts on day 34 of pregnancy (Farmer 2003). High circulating IGF-I concentrations have been described in obesity (Scacchi et al 1999) and were thought to be achieved via a stimulatory effect of leptin on ST release. Indeed, Guay et al (2001) reported greater concentrations of leptin in Meishan crossbred than LW crossbred gilts on day 25 of pregnancy, yet values in late-gestation need to be obtained.…”
Section: Repeated Injections Of Grf Increase Somatotropin (St) Concenmentioning
confidence: 93%
“…Rehfeldt et al (2001b) reported that maternal treatment with ST in early gestation increased total fiber number in the semitendinosus muscle of neonates, but there was no increase in the psoas major muscle. The authors concluded that pST could be muscle-specific with regard to its ability to increase fiber number.…”
Section: Repeated Injections Of Grf Increase Somatotropin (St) Concenmentioning
confidence: 99%